Coastal Wetland Soil Carbon Storage at Mangrove Range Limits in Apalachicola Bay, FL: Observations and Expectations - Steinmuller, Havalend E.; Breithaupt, Joshua L.; Engelbert, Kevin M.; Assavapanuvat, Prakhin; Bianchi, Thomas S. (Frontiers in Forests and Global Change, 2022)
Globally, mangrove range limits are expanding often at the cost of adjacent coastal ecosystems including saltmarshes, potentially leading to a change in ecosystem services, such as organic carbon (OC) sequestration. Studies in the southeastern US have focused almost exclusively on Avicennia germinans range expansion, the most cold-tolerant mangroves in North America. The Apalachicola Bay region of north Florida represents the northern range limit of mangroves in the Gulf of Mexico, and uniquely also includes Rhizophora mangle. The objective of this research was to quantify soil OC density beneath both mangrove species and compare results with soils beneath two commonly adjacent native tidal saltmarsh species: Juncus roemerianus and Spartina alterniflora. Dominant plant taxa were not a significant predictor of soil OC density, highlighting the relative importance of site-specific environmental attributes as controls on soil properties. Soil profile δ13C compositions included a range of values reflective of C3 and C4 plant inputs, suggesting that shifts in plant taxa, both from marsh to mangroves and between marsh species, have been occurring at all sites in this study. These findings support much of the literature on mangrove encroachment, which indicates mangrove soil OC concentrations, densities, or stocks are less than or equal to that of co-located tidal marsh habitats. Through a systematic review, the potential of several proposed explanatory variables (climate, environmental setting, plant physiology and productivity, and duration of encroachment) were identified to evaluate how soil OC density in mangrove habitats might increase over time, which is critical to forecasting how continued mangrove expansion might affect blue C storage as these habitats evolve.